1968
DOI: 10.1104/pp.43.5.683
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Mode of Action of Tomatine as a Fungitoxic Agent

Abstract: Abstract. Removal of 1 or more sugar residues from the a-tomatine molecule markedly decreased its fungitoxicity. While partial hydrolysis of a4omatine did not greatly affeot its surfaotant properties, it did destroy the ability of this alkaloid to form a complex with cholesterol. Only unprotonated a-tomatine was capable of binding cholesterol; the protonated form did not. Since a-tomatine was far more toxic at a high pH than at a low pH, this suggests that the unprotonated alkaloid is the active form and that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1

Year Published

1975
1975
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(60 citation statements)
references
References 8 publications
2
57
1
Order By: Relevance
“…16,17 Similarly, in a preliminary study, we also found that growth of rumen cellulolytic bacteria was unaffected by purified smilagenin or sarsasapogenin (Wang et al, unpublished data). It is reasonable to assume, therefore, that saponin present in a ruminal supernatant fraction (i.e.…”
Section: Centrifugation For Separating Sapogenin From Saponin and Itssupporting
confidence: 54%
See 1 more Smart Citation
“…16,17 Similarly, in a preliminary study, we also found that growth of rumen cellulolytic bacteria was unaffected by purified smilagenin or sarsasapogenin (Wang et al, unpublished data). It is reasonable to assume, therefore, that saponin present in a ruminal supernatant fraction (i.e.…”
Section: Centrifugation For Separating Sapogenin From Saponin and Itssupporting
confidence: 54%
“…Similarly, others have found that once deglycosylated, saponins no longer exhibit their antifungal properties. 16,17 Thus, further definition of the mechanisms of microbial metabolism of saponins in the rumen could provide valuable information with regard to their potential to favorably manipulate ruminal fermentation. This study was conducted with the objective of modifying the spectrophotometric method of Baccou et al 12 to enable measurement, in ruminal fluid, of steroidal saponin and of sapogenin, its deglycosylated, insoluble form, and to use the modified procedure to assess the deglycosylase activity of ruminal microbes by comparing the activities in cell-associated and extracellular enzyme fractions.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding these aspects and the definition of phytoalexins as postulated by Mü ller and Börger (52), we propose that we have identified a new phytoalexin in barley. The inhibitory effect of p-CHA on appressoria and haustoria formation of E. graminis is in the tested range of 0.1-200 M and is comparable with known antimicrobial compounds such as camalexin in A. thaliana, pisatin in P. sativum, tomatine in Solanum lycopersicum, and avenacin in Avena sativa (53)(54)(55)(56). However, in the applied concentrations of 200 M, p-CHA did not seem to reduce mycelial growth on leaves after 7 days.…”
Section: Discussionmentioning
confidence: 73%
“…Glycoalkaloids conferred no antifungal properties against Phytophthora infestans in vitro (Holland & Taylor, 1979) since this pathogen detoxifies glycoalkaloids via production of extracelluar glucosidase enzymes which hydrolyse the sugar moiety from the aglycone molecule and in turn reducing the sterol binding properties (Roddick & Rijnenberg, 1986) and toxicity of glycoalkaloids (Arneson & Durbin, 1968). Consequently, reduction in growth of Phytophthora infestans may result from increases in compounds such as chlorogenic acid following illumination.…”
Section: Discussionmentioning
confidence: 99%